Longitudinal trajectories of memory among middle-aged and older people with hearing loss: the influence of cochlear implant use on cognitive functioning - Völter, Christiane; Götze, Lisa; Dazert, Stefan; Thomas, Jan Peter; Kamin, Stefan Thomas (Frontiers in Aging Neuroscience, 2023)
Introduction: Cochlear implants (CI) are the gold standard intervention for severe to profound hearing loss, a known modifiable risk factor for dementia. However, it remains unknown whether CI use might prevent the age-related cognitive decline. Recent studies are encouraging but are limited, mainly by short follow-up periods and, for ethical reasons, lack of appropriate control groups. Further, as age-related cognitive decline is multifaceted and not linear, other statistical approaches have to be evaluated. Material and Methods: Immediate and delayed recall as measures of cognitive function were assessed in 75 newly implanted CI users (mean age 65.41 years ±9.19) for up to 5 years (mean 4.5 ±0.5) of CI use and compared to 8,077 subjects of the same age range from two longitudinal cohort studies, the Health and Retirement Study (HRS) and the English Longitudinal Study of Ageing (ELSA). Linear and quadratic changes in cognitive trajectories were analyzed in detail using mixed growth model, considering possible confounders.Results: For CI users, the linear time slope showed a significant improvement in this specific domains analyzed (recall and delayed recall) over time. The quadratic time slope clearly indicated that the predicted change after CI provision followed an inverted U-shape with a predicted decline two years after CI provision. In the hearing-impaired group, a significant decline over time was found, with steeper declines early on and the tendency to flatten out in the follow-up.Conclusion: CI use seems to boost cognitive trajectories in the first years after implantation. However, long-term prevention of dementia seems to need far more than restoration of hearing loss.